Triboelectric nanogenerator based on degradable materials. Issue 1 (28th December 2020) - Chao, Shengyu; Ouyang, Han; Jiang, Dongjie; Fan, Yubo; Li, Zhou
Abstract: Green and eco‐friendly energy technology are crucial to reduce environmental pollution caused by fossil fuels. Triboelectric nanogenerator (TENG), as an emergency green energy technology, which can get the energy from the surrounding environment and organism. The development of TENG based on degradable materials strongly promote the next‐generation green energy technologies that will effectively avoid pollution and hazards caused by metal and hardly degradable plastic materials. In this review, we summarize the TENG based on degradable materials and its applications. The typical degradable materials for TENG are animal‐based degradable material, plant‐based degradable material, and artificial degradable material. We provide perspectives on the challenges and potential solutions associated with the next‐generation degradable TENG. Beyond the material issue, we highlight the full biodegradable devices that show the healthcare function in vivo. Abstract : With the continuous depletion of environmental resources, DB‐TENG, as a green energy, began to be widely used in all fields of society. Here, degradable materials which were used as triboelectric layers were classified into three categories. Besides, DB‐TENG can be used to complete functions such as energy harvesting, signal sensing, and medical care.